1991
DOI: 10.1007/bf01244944
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic measures in suicide brain: 5-HT1A binding sites in frontal cortex of suicide victims

Abstract: The density of 5-HT1A binding using 3H-8-hydroxy-2-(di-n-propyl-amino) tetralin (8-OH-DPAT) as binding ligand, was studied in human frontal cortex of suicide victims and normal controls who died due to medical disease or accidentally. There was no difference in the maximum number of binding site (Bmax) or Kd (an inverse measure of affinity) of 5-HT1A receptor binding sites between normal controls and the entire group of suicide victims. However, nonviolent suicides had significantly higher Bmax (22-25%) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 46 publications
7
64
0
3
Order By: Relevance
“…51 In contrast, most, but not all, studies in frontal cortex have reported no changes of postsynaptic 5-HT 1A serotonin receptors in depressed suicide victims. [52][53][54][55][56][57] The present study agrees with these data and demonstrates the unaltered functional status of these postsynaptic 5-HT 1A serotonin receptors in suicide victims with mood disorders. Recently, a widespread reduction in 5-HT 1A serotonin receptor binding potential has been drawn from positron emission tomography analysis of 25 depressed patients (unmedicated or medicated) with the selective antagonist [ 11 C]WAY-100635, 58 which could reflect either a reduction in the number of 5-HT 1A serotonin receptors or a decrease in receptor affinity.…”
Section: Molecular Psychiatrysupporting
confidence: 80%
“…51 In contrast, most, but not all, studies in frontal cortex have reported no changes of postsynaptic 5-HT 1A serotonin receptors in depressed suicide victims. [52][53][54][55][56][57] The present study agrees with these data and demonstrates the unaltered functional status of these postsynaptic 5-HT 1A serotonin receptors in suicide victims with mood disorders. Recently, a widespread reduction in 5-HT 1A serotonin receptor binding potential has been drawn from positron emission tomography analysis of 25 depressed patients (unmedicated or medicated) with the selective antagonist [ 11 C]WAY-100635, 58 which could reflect either a reduction in the number of 5-HT 1A serotonin receptors or a decrease in receptor affinity.…”
Section: Molecular Psychiatrysupporting
confidence: 80%
“…Another autoradiographic post-mortem examination with [ 3 H]8-OH-DPAT found a significant negative correlation between age and the number of 5-HT 1A receptors in the frontal cortex of suicide victims, but not in a control group (Lowther et al 1997). In contrast, an earlier study had reported a significant negative correlation of age and 5-HT 1A B max in frontal cortex of a control group but not in suicide victims (Matsubara et al 1991). The interpretation of these postmortem results is compromised by the fact that the agonist ligand 8-OH-DPAT measures 5-HT 1A receptors only in the high-affinity state.…”
Section: Discussionmentioning
confidence: 82%
“…Post-mortem studies show a decline in 5-HT 1A receptor number with age (Dillon et al 1991;Lowther et al 1997;Matsubara et al 1991). However, these studies have either used 8-OH-DPAT, an agonist ligand, which measures 5-HT 1A receptors in the high affinity state, or spiperone, an antagonist, which lacks specificity.…”
mentioning
confidence: 99%
“…Indeed, age-associated changes in serotonergic function could have a substantial impact on the capacity of the elderly to resist depression and to respond to serotonergically mediated antidepressant pharmacotherapy. Some postmortem studies (Arango et al, 1997;Dillon et al, 1991;Marcusson et al, 1984a;Matsubara et al, 1991), but not others (Cheetham et al, 1990;Palego et al, 1997) have found aging effects in 5-HT 1A receptor density. Two PET studies using the selective 5-HT 1A receptor antagonist [ 11 C]WAY 100635 have shown an influence of age on 5-HT 1A binding (Meltzer et al, 2001;Tauscher et al, 2001).…”
Section: Introductionmentioning
confidence: 99%